PENERAPAN BELAJAR YOGA SEBAGAI PENINGKATAN KECERDASAN EMOSI GURU DAN MURID - Werdi Purniasih, Ida Ayu Komang; Suyanta, I Wayan (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
This research focuses on the study of the application of yoga learning carried out by teachers and students. Their life is done by meditation and yoga asana before starting learning. The literature review is related to emotional intelligence of early childhood and Yoga Sutra Patanjali. The method in this study used observation analysis, pre test and post test. Involving students and teachers from Madhu Vidya Kindergarten, totaling 57 children and 3 teachers. This study shows that there is (1) recognizing the form of self-emotion, (2) increasing the ability of teachers and students in managing emotions in themselves, (3) building relationships and communicating with others.